Role of Ultrahigh Frequency Ultrasound in Evaluating Experimental Flaps - Morarasu, Stefan; Ghetu, Nicolae; Coman, Corneliu George; Morarasu, Bianca Codrina; Boicu, Daniel; Spiridon, Irene Alexandra; Gardikiotis, Ioannis; Danciu, Mihai; Pieptu, Dragos (Journal of Reconstructive Microsurgery, 2020)
Background Experimental flap follow-up needs faster, safer, and less invasive techniques that can be easily correlated to clinical procedures. For this reason, we aimed to test the role of ultrahigh frequency ultrasound in follow-up of flap viability. Further on, we aimed to analyze if the chimeric groin flap can be mobilized in a sandwiched position without affecting its vascular supply by twisting its pedicle.Methods A total of 12 male Wistar rats, split into three groups, were used. Group A (n = 4) had the chimeric groin flap repositioned in a sandwich position on the anterior abdominal wall and underwent ultrahigh frequency ultrasound follow-up at days 10 and 14. Group B (n = 4) also had the flaps sandwiched, however, at day 14 the vascularity of flaps was proven by infusion of nontargeted ultrasound contrast agents, after which flaps were sent for histological analysis. Group C (C1 n = 2, C2 n = 2) was the control group. In C1 the chimeric groin flap was harvested and sent for histology on day 0, acting as a histological benchmark of flap viability, and in C2 the chimeric groin flap was re-sutured in its anatomical position and after 14 days, flaps were harvested and sent for histological analysis, acting as a direct control for Group B.Results Ultrasound showed constant vascular flow in both adipose and skin flaps in the sandwiched position. Microbubble study showed diffuse perfusion within flaps. Ultrasound measurements of flow velocity, flap volume, and percentage of vascularity showed a decrease in flap volume and increase in vascularity over 14 days. Histology showed similar viability in both groups.Conclusion Ultrahigh frequency ultrasound may be a valuable tool for postoperative flap assessment, while the chimeric flap can be moved freely in a sandwich position making it suitable for adding tissue substitutes within its components.
Keywords: ultrasound; flaps; experimental surgery